2020
DOI: 10.1097/fjc.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Ticagrelor in Patients With High Ischemic Risk and Previous Myocardial Infarction: A Multicenter Prospective Real-World Observational Study

Abstract: Prolonged dual antiplatelet therapy after 12 months in patients with previous myocardial infarction (MI) is attractive to reduce long-term ischemic complications. In the PEGASUS-TIMI 54, the use of low-dose ticagrelor (60 mg b.i.d.) plus aspirin after 12 months from MI reduced the risk of ischemic events, at the price of limited increase on bleeding complications. However, data on the use of low-dose ticagrelor in real-world practice lack. We aim at providing data on prescription/eligibility criteria and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Clinical factors increasing the risk of bleeding (e.g., age > 75 years old, female sex, prior stroke, body weight < 60 kg, renal dysfunction) and ischemia (e.g., diabetes mellitus, peripheral artery disease, prior cardiovascular event, prior coronary revascularization, left main stenting, bifurcation stenting) should be considered in the recommendation of oral antiplatelet therapy [ 7 , 15 – 23 ]. In clinical practice, carefully selected patients may derive the greatest benefit from more intense antithrombotic therapy after AMI [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical factors increasing the risk of bleeding (e.g., age > 75 years old, female sex, prior stroke, body weight < 60 kg, renal dysfunction) and ischemia (e.g., diabetes mellitus, peripheral artery disease, prior cardiovascular event, prior coronary revascularization, left main stenting, bifurcation stenting) should be considered in the recommendation of oral antiplatelet therapy [ 7 , 15 – 23 ]. In clinical practice, carefully selected patients may derive the greatest benefit from more intense antithrombotic therapy after AMI [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we could not provide comparative cardiovascular effects of SGLT-2 inhibitors between high-intensity and low-moderate-intensity statin treatment or between statin users and nonusers in our study. In addition, diabetic patients may benefit from long-term antiplatelet therapy, and diabetes is a key criterion for choosing continuation of DAPT in life [ 50 ]. Cesaro et al [ 50 ] showed that in a real-world study, including patients with previous MI, low-dose ticagrelor for prolonged dual antiplatelet therapy showed to be effective and safe, with no major bleeding occurring at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetic patients may benefit from long-term antiplatelet therapy, and diabetes is a key criterion for choosing continuation of DAPT in life [ 50 ]. Cesaro et al [ 50 ] showed that in a real-world study, including patients with previous MI, low-dose ticagrelor for prolonged dual antiplatelet therapy showed to be effective and safe, with no major bleeding occurring at follow-up. Therefore, the duration and kinds of DAPT in patients with AMI is very important.…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized PEGASUS-TIMI 54 (Prevention of Cardiovascular Events in Patients With Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin–Thrombolysis in Myocardial Infarction 54) trial ( n = 21,162), the use of low-dose ticagrelor (60 mg twice a day) plus aspirin after 1–3 years from MI reduced the risk of ischemic events, at the price of limited increase on serious bleeding complications [ 20 ]. In addition, a recent Western real-world observational study provided that low-dose ticagrelor after 12 months from MI showed to be effective and safe, with no major bleeding occurring at follow-up [ 21 ].…”
Section: Discussionmentioning
confidence: 99%